2004
DOI: 10.1111/j.0022-1112.2004.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between environmental factors, smolt size and the survival of wild and reared Atlantic salmon from the Simojoki River in the Baltic Sea

Abstract: The survival of Atlantic salmon Salmo salar in the Baltic Sea was examined in relation to smolt traits (length and origin) and annual environmental factors [sea surface temperature (SST) and seasonal North Atlantic Oscillation (NAO) index], and prey fish abundance (herring Clupea harengus and sprat Sprattus sprattus) in the main basin and the southern Gulf of Bothnia. The study was based on recapture data for Carlin-tagged hatchery-reared and wild smolts from the Simojoki, a river flowing into the northern Gul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 32 publications
5
59
0
Order By: Relevance
“…But signifi cant correlations with the NAO have not always been the outcome. For example, for hatchery -reared and wild Baltic post -smolts, Kallio -Nyberg et al (2004) found no correlation between the NAO and survivorship of wild smolts, but did note a positive correlation between year -class survivorship and July SST -immediately after smolt entry to sea water -perhaps indicating a detrimental effect of cold summers. Similarly, Niemel ä et al (2004) found no correlation between the NAO and salmon catches in the rivers Teno and Naatamojoki (northern Finland), the stocks of which migrate to the Barents Sea and show large natural fl uctuations.…”
Section: Amo Departurementioning
confidence: 82%
See 3 more Smart Citations
“…But signifi cant correlations with the NAO have not always been the outcome. For example, for hatchery -reared and wild Baltic post -smolts, Kallio -Nyberg et al (2004) found no correlation between the NAO and survivorship of wild smolts, but did note a positive correlation between year -class survivorship and July SST -immediately after smolt entry to sea water -perhaps indicating a detrimental effect of cold summers. Similarly, Niemel ä et al (2004) found no correlation between the NAO and salmon catches in the rivers Teno and Naatamojoki (northern Finland), the stocks of which migrate to the Barents Sea and show large natural fl uctuations.…”
Section: Amo Departurementioning
confidence: 82%
“…Direct physiological effects of temperature have often been inferred, especially for smolts fi rst entering sea water (e.g. Narayanan et al 1995 ;Kallio -Nyberg et al 2004 ;Jutila et al 2005 ; Section 16.6 ), and the importance of indirect effects -perhaps manifest as ' bottom -up ' impacts through alterations in prey availability -has long been suspected or observed (e.g. Todd et al 2008 ).…”
Section: Ocean C Limate I Nfl Uences On R Un -T Iming and A Dult A Bumentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge of the ecology of wild salmon is important to improve enhancement and management techniques because wild salmon populations have evolved to adapt to the environmental conditions of the local area. These same factors affecting the marine survival of wild salmon have also been investigated [10][11][12][13][14][15][16]. The timing of smolt migration varies with species, age, latitude, and the specific estuarine-coastal area [17,18], which is thought to be population specific [19], and the timing of seaward migration and ocean entry also strongly affect the survival of smolts.…”
Section: Introductionmentioning
confidence: 99%